EFL Teachers’ Approaches for Continuing Professional Development - Fitri Aprianti; Eline Rozaliya Winarto; Dila Charisma (Universitas Muhammadiyah Jember, 2021)
Continuing professional development (CPD) is imperative for teachers. English language teachers are not exceptions. In continuing their professional development, teachers actually have flexibility to choose either training or self-directed CPD approach. Therefore, it is assumed that depending on the gender and the career developmental stage that they are in, teachers may choose different CPD approach. Thus, this study was aimed to see the relationship between teachers’ career developmental stage, gender and their selection of CPD approaches. In order to achieve that, this study employed descriptive quantitative approach. The participant involved were 54 EFL teachers in Majalengka, West Java. The data were collected by using questionnaires. Chi-square was used in order to test the three hypotheses. The result revealed that the teachers mainly showed positive comments on CPD. Furthermore, it was found that there was a significant relationship between the teachers’ career developmental stages and CPD approaches. On the other hand, the findings signified that there was no relationship between gender of the teachers and their CPD approaches. As the recommendation it is expected that the teachers could maintain and regulate their commitment on continuing professional development. In addition, the government, especially the Indonesian Ministry of Education and Culture is also expected to provide wider variety of professional development approaches so as to bridge the diverse preferences for continuing professional development (CPD) of the teachers in Indonesian setting.